Leaf gas exchange and stomata properties of oil palm seedlings (Elaeis guineensis Jacq.) progenies exposed to elevated carbon dioxide - Ibrahim, Mohd Hafiz; Jaafar, Hawa Z. E.; Harun, Mohd Haniff (Sciencedomain International, 2017)
Aims: An experiment was carried out to examine the impact of increased CO2 level on gas exchange characteristics and stomatal properties of three oil palm progenies (Deli URT, Deli Yangambi and Deli AVROS). The seedlings were exposed to three CO2 enrichment treatments: ambient CO2 (400 µL L-1), twice (800 µL L-1) and thrice ambient CO2 (1200 µL L-1) for six days a week for three months. Study Design: The experiment used a 3x3 Randomized Complete Block Design (RCBD) in factorial split plot arrangement with the CO2 levels as the main plot and progenies as the sub plot replicated three times. Each treatment contained 10 seedlings. Place and Duration of Study: Malaysian Palm Oil Board, (MPOB) Headquarters, between January to March 2009. Methodology: Carbon dioxide at 99.8% purity was provided from a high pressure CO2 cylinder and injected through a pressure regulator into fully sealed growth compartments. The flow of CO2 in the chamber was automatically controlled by a CO2 P.P.M. Controller ™ (R and M Supply Inc. USA). Seedlings were exposed to elevated CO2 for 2 hours per day from 0800 in the morning to 1000 continuously for six days every week. The leaf gas exchange was measured using a closed system, infra-red gas analyzer LICOR 6400 Portable Photosynthesis System (IRGA: LICOR Inc. Nebraska, USA). The net photosynthesis rate (A), transpiration rate (E), stomata conductance (gs) and intercellular CO2 (Ci) were simultaneously recorded. Stomata densities were examined by means of peel surface imprints made using clear nail varnish (cellulose acetate). Before peeling off, the layers with the impression imprinted were then placed on 1 mm2 graduated slide. All stomata were counted in six field to give a mean value for each sample. Results: Significant interactions between CO2 and progenies for gas exchange attributes were observed except for stomata density. Increased CO2 significantly (p≤0.05) affected net photosynthesis (A), stomata conductance (gs), transpiration rate (E), instantaneous water use efficiency (WUE), intercellular CO2concentration (Ci), adaxial, abaxial and total stomata density. As CO2 concentration increased, A, and WUE increased. It was also observed that stomata conductance and transpiration rate reduced and could be explained by stomata closure and declining stomata densities (abaxial, adaxial, total) under elevated CO2. The decreased stomata density (pores per mm2) was likely due to greater leaf expansion as showed by increased in total leaf area per seedling. Conclusion: Results showed that the increase in WUE was due more to an increase in net photosynthesis (A) than to a reduced transpiration rate (E). The experiment showed there was no significant difference (p≤0.05) between 800 and 1200 µL L-1 CO2 treatments in any of the variables measured.